The Urgency of Sharia Compliance Regulation in Indonesia's Digital Economy - Muzalifah Muzalifah (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2026)
Digital economic transactions in Indonesia are experiencing rapid development, but the legal system is not yet able to guarantee Sharia compliance for digital transactions. The objective of this study is to map the legal relationship between the Financial Services Authority (OJK) and Bank Indonesia (BI) regulations, as well as the DSN-MUI Fatwa regarding digital transactions and compliance with Sharia principles in those transactions, and to describe these relationships based on survey results. The researchers used a qualitative research method with a normative-empirical approach. Data collection techniques included observation, interviews, and documentation. Data validation utilized source triangulation. Data analysis consisted of data presentation, data categorization, and conclusion drawing. The study found that there is legal harmonization between the DSN-MUI fatwas and the OJK and BI regulations regarding digital economic transactions and the application of sharia principles. This statement is based on findings from several fatwas issued by the DSN-MUI and articles in OJK and BI regulations, which substantially require sharia compliance in every digital transaction. Meanwhile, based on the survey results, 92.5% of the 121 respondents had conducted digital transactions; 90.41% of them stated that they conducted digital transactions based on sharia principles. Thus, legal harmonization can reduce violations of Sharia principles in digital transactions, support the existence of Islamic law in Indonesia's digital transaction system, and gradually contribute to increasing national financial inclusion. However, efforts to improve digital financial literacy, disseminate regulations, and improve financial infrastructure that can reach all levels of society in Indonesia are needed.